Harvesting methods on physical and physiological quality of Panicum maximum seeds - Carla G. Machado; Simério C. S. Cruz; Givanildo Z. Silva; Luciana C. Carneiro; Ingrid M. H. de L. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The quality of seeds of forage species can be influenced by the different harvesting methods used. The aim of this study was to evaluate the physical and physiological quality of seeds of Panicum maximum, cultivars ‘Massai’ and ‘Mombaça’, obtained by the methods of ground sweeping and direct heading (cutting of the panicles) of different farmers in the year 2014. The test consisted of three lots of each cultivar from seed farmers in the state of Goiás, Brazil. The experimental design was completely randomized, in 3 x 2 factorial scheme (farmer x harvesting methods) with four replicates. The following variables were analyzed: physical purity, 1000-seed weight; germination and first count of germination. At the end of the germination the percentage of dormancy and dead seeds were evaluated by the tetrazolium test of the remaining seeds, in addition to the abnormal seedlings. The data were submitted to analysis of variance and the means of the treatments were compared by Tukey test at 0.05 probability level. Seeds of P. maximum ‘Massai’ and ‘Mombaça’ collected by ground sweeping have superior physiological quality despite the low level of purity of the lots, compared to direct heading method.